The Vulnerability Scan, a Web Tool to Increase Institutional Biosecurity Resilience - Meulenbelt, Stephanie E.; van Passel, Mark W. J.; de Bruin, Arnout; van den Berg, Linda M.; Schaap, Mirjam M.; Rutjes, Saskia A.; Jacobi, André J.; Agterberg, Marja C.; de Hoog, Carin; van Willigen, Gijsbert; Kampert, Evelien; Heres, Jan H. J.; et al. (Frontiers in Public Health, 2019)
The importance of vigilance within organisations working with high-risk biological material receives increasing attention. However, an in-depth and comprehensive tool, dedicated to increase awareness of potential risks and to assess an organisation’s current biosecurity vulnerabilities, has not been available yet. We developed the “Biosecurity Vulnerability Scan”, a web tool that identifies biosecurity gaps in an organisation based on eight biosecurity pillars of good practice. Although the tool aims primarily to assist biosafety and biosecurity officers, it can also be useful to researchers working with dangerous pathogens, their principal investigators, management, or those responsible for security issues in the life sciences. Results are only stored locally and are provided in an “overview report”, which includes information on relevant risks and control measures. This can support well-substantiated decision-making on strengthening biosecurity measures within a specific organisation. The Biosecurity Vulnerability Scan is available at www.biosecurityvulnerabilityscan.nl